THE EFFECTIVENESS OF USING VISUAL AIDS INTEGRATED COMMUNICATIVE LANGUAGE TEACHING METHOD IN IMPROVING THE STUDENTS’ SPEAKING ABILITY AT THE SECOND GRADE OF SMAN 1 PINRANG - Rustan ,; Nur Asik (ETERNAL (English, Teaching, Learning and Research Journal), 2016)
This research was aimed to determine the effectiveness of usingvisual aids integrated communicative language teaching method in improving thestudents’ speaking ability at the second grade of SMAN 1 Pinrang. Therefore, theprinciple research problem was only one in this research, that is to what extent isusing visual aids integrated communicative language teaching method effective inimproving the students speaking ability at the second grade of SMAN 1 Pinrang?The researcher applied experimental method with the non-equivalent controlledgroup design. The population of this research was the second grade students atSMAN 1 Pinrang, which consist of 150 students. The sample was taken by usingpurposive sampling. So, the researcher took two classes in this research, one classas experimental class which consisted of 30 students and one class as controlledclass. The data were collected through pre-test and post-test. Based on the researchfindings, from the test, the researcher concluded that the use of visual aidsintegrated communicative language teaching method effective in improving theirachievement in speaking ability, especially for fluency and accuracy. It proved fromthe mean of the both of classes, which was the mean score of post -test ofexperimental class was 59,2 while the mean score of control class was 45.6. Theresult of t-test also shown that the visual aids integrated communicative languageteaching method is effective in improving students’ speaking ability because t -test,4.94, is higer than t-table, 2.000 (4.94>2.000). The research result of this studyimplies that English teachers should use communicative language teaching methodintegrated visual aids to develop their techniques and methods in teaching speaking,the students use pictures and videos in improving their speaking ability as it canhelp them with the new ideas, vocabularies, and pronunciations, the futureresearcher develops some dimensions which have not been developed in thisresearch like using different students’ population or students’ condition viewedfrom the students’ habit or interest.